EFFECT OF SEQUENTIAL APPLICATION OF HERBICIDES ON WEEDS AND PRODUCTIVITY OF SPRING PLANTED SUGARCANE (SACCHARUM OFFICINARUM L.) - CHOUDHARY, H. R.; SINGH, R. K. (The Bioscan, 2016)
The study was carried out during the spring seasons of 2011-12 and 2012-13 to the effect of sequential application of herbicides on weeds and productivity of spring planted sugarcane (Saccharum officinarum L.). Results showed that the minimum weed density at 90 DAP, weed control efficiency (94.53%) at 90 DAP and weed index were significantly highest with conventional practice (three hoeings) at 30, 60 and 90 DAP. Weight of millable cane, cane yield (135.32 t/ha), green tops yield, trash yield, biological yield and harvest index were found highest under conventional practice (three hoeings) at 30, 60 and 90 days after planting of sugarcane. Among the herbicides, the sequential application of ametryne @ 2.4 kg a.i./ha at 30 DAP fb 2,4-D @ 1.0 kg a.i./ha at 60 DAP of sugarcane observed as the second best treatment with lower weed density at 90 DAP, weed control efficiency (85.61%) at 90 DAP weed index (8.61%) and cane yield (123.66 t/ha).